2012
DOI: 10.1590/s0104-66322012000200005
|View full text |Cite
|
Sign up to set email alerts
|

Supercritical CO2 extraction of raw propolis and its dry ethanolic extract

Abstract: -Three types of propolis extract were prepared and analyzed with respect to their global extraction yields and with respect to the concentration of the following markers: 3,5-diprenyl-4-hydroxycinnamic acid; 3-prenyl-4-hydroxycinnamic acid; 4-hydroxycinnamic acid and 4-methoxy-3,5,7-trihydroxyflavone. The extract EEP (ethanolic extract of propolis) was obtained by the conventional method from raw propolis using ethanol as solvent. The extracts (SFE) were obtained by supercritical solvent extraction from the ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 29 publications
2
20
1
Order By: Relevance
“…The fruits of P. emblica are highly nutritive, being rich sources of vitamin Traditional methods such as soxhlet and conventional heat-reflux extraction for the recovery of bioactive compounds are laborious (Paviani et al, 2012). They require heavy capital investments, longer extraction time, higher solvent consumption and, therefore, are less friendly to the environment (Barba et al, 2015;Dong et al, 2014;Li et al, 2013;Liao et al, 2015;Wakte et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The fruits of P. emblica are highly nutritive, being rich sources of vitamin Traditional methods such as soxhlet and conventional heat-reflux extraction for the recovery of bioactive compounds are laborious (Paviani et al, 2012). They require heavy capital investments, longer extraction time, higher solvent consumption and, therefore, are less friendly to the environment (Barba et al, 2015;Dong et al, 2014;Li et al, 2013;Liao et al, 2015;Wakte et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The low mass yield of propolis extract by SFE has been demonstrated in other studies, which may be related to the fact that propolis is not very soluble in supercritical CO 2 but can be much more soluble in a mixture containing CO 2 and ethanol [ 51 , 52 , 53 ]. SFE is considered a very efficient technique in terms of selectivity for the extraction of target compounds, as well as for the separation and fractionation of different classes of compounds; however, depending on the polarity of these compounds, it is necessary to add small amounts of a modifier or cosolvent to the system to improve process yield [ 54 ].…”
Section: Resultsmentioning
confidence: 92%
“…In a comparative study of extraction methods to obtain extracts from green propolis by SFE, Monroy et al [ 36 ] found that when using 32% of the solution containing 80% ethanol and water as a cosolvent, a 43% increase in yield was obtained compared to SFE without the cosolvent, in addition to 220 mg GAE/g of phenolic compounds (extraction conditions 50 °C and 250 bar). Paviani et al [ 53 ], when adding 15% ethanol as a cosolvent to obtain extracts of green propolis (extraction conditions 50 °C and 250 bar), obtained an increase of 43.7% compared to the same process without the use of a cosolvent. The influence of the addition and concentration of cosolvent on supercritical CO 2 extraction was also shown for other natural matrices [ 62 ], demonstrating the importance of these modifiers to improve the extraction capacity of polar compounds.…”
Section: Resultsmentioning
confidence: 99%
“…Influence of temperature and pressure on the SFE yield at constant solvent flow rate (Q CO2 = 6.0 mL min -1 ). (Paviani et al, 2012) promoted by an increase in the pressure at constant temperature. The positive effect of temperature observed in experiments 6 and 8 can be explained by the fact that, at higher temperatures, the solvent viscosity is lower and the vapor pressure of the extract greater, and consequently there is an increase in the solvent diffusivity (Goleroudbary and Ghoreishi, 2016).…”
Section: Extraction Yieldmentioning
confidence: 99%